THE PARTICULARITIES OF THE VOCABULARY OF THE JOURNALISTIC STYLE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The presented article defines the style of journalism and press and deals with its lexical peculiarities in German with examples from the German-language press.